High prevalence of late diagnosis of HIV in Mexico during the HAART era - Brenda Crabtree-Ramírez; Yanink Caro-Vega; Francisco Belaunzarán-Zamudio; Juan Sierra-Madero (Instituto Nacional de Salud Pública, 2012)
OBJECTIVE: To evaluate the prevalence of late HIV diagnosis (CD4<200 cell/mm³) in an HIV clinic in Mexico City between 2001-2008, to assess changes in this prevalence across the study period, and to determine the risk factors associated to late testing (LT). MATERIALS AND METHODS: Cross-sectional analysis including all patients recently diagnosed as HIV. We estimated the proportion of LT patients and compared demographic characteristics between those and all other. We determine the risk factors associated to LT using logistic regression methods. RESULTS: Sixty one percent of LT patients present when are diagnosed for the first time. The prevalence did not decrease between 2001 and 2008 (p=0.37). Older age (OR: 2.4; 95%CI 1.2-4.7), unemployment (OR: 1.75; 95%CI 1.12-2.75) and less than nine years of education (OR: 2.44; 95%CI 1.37-4.33) were independently associated to LT, in a multivariate analysis. CONCLUSION: LT has high prevalence in Mexico, this impact on antiretroviral effectiveness and perhaps on HIV transmission. Policies for HIV-prevention in Mexico need to be modified to reduce LT prevalence including more aggressive strategies of testing. OBJETIVO: Estimar la prevalencia de diagnóstico tardío (DT) (CD4<200 cel/mm³) de VIH en una clínica en la Ciudad de México entre 2001 y 2008, evaluar cambios en la prevalencia en este periodo y determinar factores de riesgo asociados con el DT. MATERIAL Y MÉTODOS: Mediante un estudio de cohorte transversal de pacientes de VIH se estimó la proporción de pacientes con DT y se compararon sus características demográficas con pacientes sin DT. Se evaluaron los factores de riesgo asociados a DT usando regresión logística. RESULTADOS: Se encontró una prevalencia de DT de 61%, sin cambios entre 2001-2008 (p=0.37). Mayor edad (RM: 2.4; 95%IC 1.2- 4.7), desempleo (RM: 1.75; 95%IC 1.12-2.75) y menos de nueve años de educación (RM: 2.44; 95%IC 1.37-4.33) fueron independientemente asociados a DT. CONCLUSIONES: El DT tiene alta prevalencia en México. Esto impacta en la efectividad de tratamiento antirretroviral y posiblemente en la transmisión del VIH. Deben dirigirse políticas de prevención a reducir el DT mediante estrategias agresivas de diagnóstico.